AN ANALYSIS OF LANGUAGE STYLE OF TEENAGERS FOUND IN FACEBOOK STATUS - Indra Indra; Hamzah Hamzah (English Language and Literature, 2018)
The research aimed to find the types of language style and the frequency of the style used by facebook users in Indonesia. The source of data in this research is facebook users in Indonesia. This research focused on language style used by facebook users from the teenager to pre adult users in Indonesia. The writer used descriptive method which is describing the phenomenon based on the source of data. This research analyzed the status of the facebook users to find the types of language style and the most frequency style used by facebook users in Indonesia. On the analysis, the writer found that there are four language styles namely formal, consultative, casual, and intimate. Then, casual style is the mostly language style used by the speakers with percentage is about 70%. Furthermore, the writer found that the causes of casual is the mostly used by facebook users